A simple proof of the Radó and Král theorems on removability of the zero locus for analytic and harmonic functions - Pokrovskii, A.V. (Reports of the National Academy of Sciences of Ukraine, 2015)
A unified approach to the proof of the Radó and Král theorems on removability of the zero locus for analytic and harmonic functions is proposed.